Nano-Encapsulation Systems Improve Drug Delivery and Solubility - TAOUZINET, Lamia (Biopolymer Applications Journal, 2022)
Size reduction is one of the most often utilized and important unit processes in pharmaceutical manufacture. It contributes to increased medicine safety and bioavailability, decreased toxicity, improved drug release, and improved drug formulation possibilities. Nanoencapsulation is a process that involves encapsulating a bioactive molecule in liquid, solid, or gaseous form within a matrix of inert material in order to preserve the coated component. The size of nanoencapsules can range from 1 to 1,000 nm. They have a multitude of different shapes, depending on the materials and methods used to prepare them. The main reason for nanoencapsulation species is to ensure that the encapsulated material reaches the area of action without being adversely affected by the external environment through which it passes. This research concentrated on current breakthroughs in nanoencapsulation drug systems, production, and characterization methodologies.